2017
DOI: 10.3390/tropicalmed2030040
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards Bait Station Integration into Oral Rabies Vaccination Programs in the United States: Field Trials in Massachusetts and Florida

Abstract: Bait stations for distribution of oral rabies vaccine baits are designed for rabies management in highly-developed areas where traditional distribution of oral rabies vaccine baits may be difficult. As part of national efforts to contain and eliminate the raccoon (Procyon lotor) variant of the rabies virus (raccoon rabies) in the eastern United States, the United States Department of Agriculture, Animal and Plant Health Inspection Service, Wildlife Services program, distributed vaccine baits by bait stations e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This is less labour intensive but has other potential problems, such as non-target competition for baits, or tampering by people. Measures to mitigate such issues have been evaluated in field trials in New York, Florida and Massachusetts (87,116).…”
Section: Methods and Timing Of Bait Distributionmentioning
confidence: 99%
“…This is less labour intensive but has other potential problems, such as non-target competition for baits, or tampering by people. Measures to mitigate such issues have been evaluated in field trials in New York, Florida and Massachusetts (87,116).…”
Section: Methods and Timing Of Bait Distributionmentioning
confidence: 99%
“…A comprehensive ecological understanding may inform refinement of baiting strategies for raccoons in urban and suburban environments. Bait stations require additional study, such as incorporating them with hand baiting, locating them farther from roads to potentially bolster bait encounters as suggested by (Bigler et al 2021b), and expanding on work by Bjorklund et al (2017) to improve specificity of access by raccoons. Bigler et al (2021b) found significantly greater raccoon seroconversion from helicopter bait distribution when compared to vehicle (hand) distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Such emergency responses were expensive, involving ERS activities, additional bait drops (e.g., twice a year), or higher bait densities (e.g., 150-300 baits/km 2 ), augmented with additional methods (e.g., TVR). To maximize raccoon vaccination and to help minimize bait contact by nontarget species such as humans, domestic cats, or opossums (Didelphis virginiana), bait stations were employed, particularly in suburban and urban environments (Boulanger et al 2006;Bjorklund et al 2017;Haley et al 2017;Bastille-Rousseau et al 2024).…”
Section: United Statesmentioning
confidence: 99%